Prison, Foster Care, and the Systemic Punishment of Black Mothers - Roberts, Dorothy E. (2012)
This article is part of a UCLA Law Review symposium, “Overpoliced and Underprotected: Women, Race, and Criminalization.” It analyzes how the U.S. prison and foster care systems work together to punish black mothers in a way that helps to preserve race, gender, and class inequalities in a neoliberal age. The intersection of these systems is only one example of many forms of overpolicing that overlap and converge in the lives of poor women of color. I examine the statistical overlap between the prison and foster care populations, the simultaneous explosion of both systems in recent decades, the injuries that each system inflicts on black communities, and the way in which their intersection in the lives of black mothers helps to make social inequities seem natural. I hope to elucidate how state mechanisms of surveillance and punishment function jointly to penalize the most marginalized women in our society while blaming them for their own disadvantaged positions